Identifikasi Risiko Keselamatan dan Kesehatan Kerja Pada Proses Perbaikan Kapal Riset Geomarin III dengan Metode HIRADC - Meryna Suwito; Evi Yuliawati (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2023)
The application of K3 according to standards will help workers feel safe at work and can avoid potential work accidents. Lack of awareness of the application of K3 during work can result in the emergence of hazard risks for workers. The purpose of this study is to determine the types of work activities that are at risk and determine the application of work accident control efforts in the repair process on the GEOMARIN III research ship. The method used is HIRADC (Hazard Identification Risk Assessment and Determining Control). The identification results from the deck department and machinery department obtained 13 potential hazards with risk analysis where 4 risks included in the low risk category and 9 risks included in the medium risk category. Risk control that can be done to minimize work accidents is to inspect and maintain work equipment regularly and the use of personal protective equipment (PPE) according to standards and complete consisting of safety helmets, safety shoes, safety googles, safety gloves, ear plugs and masks. This research provides concrete recommendations on how to identify and mitigate K3 risks in the repair of research vessels, as well as contributes to the development of knowledge on the application of the HIRADC method in the shipping industry.